Lanthanide Orthoantimonate Light Emitters: Structural, Vibrational, and Optical Properties - Siqueira, Kisla P. F.
Lanthanide orthoantimonates represented by the chemical formula LnSbO(4) (Ln are all the lanthanides elements with exception of cerium and promethium) were synthesized via solid-state reactions. The crystalline structures of LnSbO(4) were determined by high-resolution Synchrotron X-ray diffraction and the Rietveld method. The samples exhibited monoclinic structures with two different arrangements as a function of the ionic radius of the lanthanide metal. For compounds with the largest ionic radii (Ln = La and Pr), the P21/n space group was determined, while compounds with intermediate and smallest ionic radii (Ln = NdLu) were described under the P2(1)/c setting. Raman spectroscopy was employed to study the vibrational features of all compounds, allowing us to determine the characteristic phonons for each structure and, consequently, to establish the relationship between chemical environment and vibrational properties. Optical features of typical SmSbO4 and TbSbO4 were thoroughly investigated, and the results indicate that the orthoantimonates are promising luminescent inorganic materials. The photoluminescence spectra (emission and excitation) of both compounds were obtained as a function of temperature under ultraviolet radiation, showing strong orange (Sm) and green (Tb) emissions, respectively. Chromaticity diagrams (CIE) were also determined for all LnSbO(4) series, aiming to bring forward the color coordinates for these emitters tuned by the chemical environment and temperature.